Farm Sangkuriang Catfish (Clarias gariepinus) for 59 Days - Nurlena Andalia; Susanti Djakfar; T. Iskandar Shah (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the cultivation of sangkuriang catfish (Clarias gariepines) for 59 days. The method used in this study is observation by collecting primary data directly from the field. During the study, the highest pool water temperature was found in the second week of 29.11 oC and the lowest temperature of pool water was found in the third week of 28.22 oC. The temperature of the pool water in the morning is lower than in the afternoon. This is influenced by sunlight that directly enters the pond which results in an increase in the metabolic process of the catfish body. The pH of Sangkuriang catfish farming pond ranges from 7.8-7.25. If the highest pH value indicates that the waters are alkaline, on the contrary, if the low pH value indicates acidic, the conclusion is that the salinity treatment of the medium does not have a significant enough effect (P<0.05) on the survival rate of catfish. Sangkuriang catfish is a type of fish that is able to survive and breed in conditions where water is less oxygen and low pH levels, in the first week the oxygen degree is 1.25 and the lowest at 0.65. Catfish tend to be more active in warm water temperatures, but they can also survive in winters with lower temperatures. However, they may become less active and require extra attention to ensure the water temperature remains within limits they can tolerate.